A long way gone : memoirs of a boy soldier - Beah, Ishmael, 1980- (2008)
This is how wars are fought now: by children, hopped-up on drugs and wielding AK-47s. Children have become soldiers of choice. In the more than fifty conflicts going on worldwide, it is estimated that there are some 300,000 child soldiers. Child soldiers have been profiled by journalists, and novelists have struggled to imagine their lives. But until now, there has not been a first-person account from someone who came through this hell and survived. Ishmael Beah, now 25 years old, tells how at the age of twelve, he fled attacking rebels and wandered a land rendered unrecognizable by violence. By thirteen, he'd been picked up by the government army, and Beah, at heart a gentle boy, found that he was capable of truly terrible acts.--From publisher description.
"Sarah Crichton books."
Originally published in hardcover: New York : Farrar, Straus & Giroux, 2007.
Keywords: Beah, Ishmael, -- 1980-; Child soldiers -- Sierra Leone -- Biography; Sierra Leone -- History -- Civil War, 1991-2002 -- Personal narratives; Sierra Leone -- History -- Civil War, 1991-2002 -- Participation, Juvenile; Sierra Leone -- Social conditions -- 1961-; Autobiographies; Personal narratives